Analisa Kebijakan Keuangan DKI Jakarta Pasca Pemindahan Ibukota Negara Ke Kalimantan Timur - Nurwidya Kusma Wardhani; Ahmad Ahsin Thohari (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research aims to examine how financial policy is analyzed in DKI Jakarta, which incidentally was the State Capital (IKN) of Indonesia when it was no longer an IKN. IKN's move to Nusantara certainly has various impacts on the people of Jakarta. Both on the social, cultural and economic sides. The economic side will certainly experience quite significant changes. Status as an IKN certainly provides added value to Jakarta. When IKN status has moved to Nusantara, economic policies will definitely follow in the areas that become IKN. In this research, we will examine financial policies for Jakarta, with a developed region, capable infrastructure, of course economic policies will be different compared to other regions even though they no longer have IKN status. The data collection method was carried out by studying literacy and statutory regulations and conducting qualitative descriptive data analysis to find out how the financial policy analysis of DKI Jakarta was carried out after the transfer of IKN to East Kalimantan.